(untitled) (Tempo e Argumento, 2024)
This article presents reflections on the intersection of public history, participatory research, oral history, and corporeality, drawing on the theoretical and methodological approaches of the Oral History and Image Laboratory at Fluminense Federal University (LABHOI/UFF, founded in 1982). It aims to examine oral history collections created through participatory research practices that incorporate embodied forms of public narrative – the recognition of pasts manifested in bodies through socially engaged work. The article explores research processes that fully acknowledge the role of the body in shaping historical subjects.